Annual Plan (2012-13) and 12th Five Year Plan (2012-17) Proposals Government of Manipur - Planning Commission (Planning Commission, 2012)
Manipur is a land with a proud history, and rich potential to transform the available national and state resources into economic growth and well being for the common man. the state is also a salad-bowl of multiple ethnicities, faiths and languages - underlining the pluralistic character of its population (27.22 lakhs by 2011 Census). People are, by and large, healthy and educated, land is resourceful and society, on the whole, caring. Yet challenges are many. the 22,327 Sq. Km of its land area is closed in from all sides by hills. There are no large waterways or effective rail transport systems, much of the reliance for inter-state communication being on the national highway system (made up of NH-39 now renamed as NH-2, NH-53 renamed as NH-37 and NH-150) that are vulnerable to hijack, by one group or the other, using access to roadway as a tool to push their political demands. This greatly affects transportation of goods and people in and out of the state, as also within the State.
Government of Manipur Planning Department